Cities as Novel Biomes: Recognizing Urban Ecosystem Services as Anthropogenic - Pincetl, Stephanie (Frontiers in Ecology and Evolution, 2015)
Urban Ecosystem Science is now an established science, arising along side the historic shift of humans to becoming in majority urban dwellers. In this Perspective I suggest there is a need to develop a new framework for UES as embedded in distinct urban biomes that can be classified by city-type and typologized. UES are largely the artifact of human decision making from what to plant where, to determining the urban infrastructure type in which UES will be placed. Developing urban typologies by climate zone, level of development, size and history will better enable the understanding of UES. I attempt to show the rise of the importance of nature, and of urban nature following the development of industrial city, and the importance of human intent in creating these urban ecosystems over time. If humans choose to manage cities through increasing UES, this will require coupled shifts, the shift in rules and regulations, goals and processes and shifts in urban form, infrastructure and function – socio-technical-ecological changes – driven by human decision-making. Such efforts will vary widely by city – by urban biome.